A Metastasizing Squamous Cell Carcinoma Arising in a Solitary Epidermal Nevus - Masami Toya; Yuichiro Endo; Akihiro Fujisawa; Miki Tanioka; Yoshiaki Yoshikawa; Takao Tachibana; Yoshiki Miyachi (Case Reports in Dermatological Medicine)
Aim. Secondary tumor rarely develops from epidermal nevus. We present a case of a metastasizing squamous cell carcinoma that developed in a solitary epidermal nevus. Case Report. An 82-years old Japanese female was presented with a red tumor on the left axilla. She reported that the tumor developed in a congenital epidermal nevus. A biopsy of the tumor showed that a well-differentiated squamous cell carcinoma (SCC) arose from the epidermal nevus. As a lymph node metastasis was found by sentinel lymph node biopsy, the patient received surgical excision of the lesion, axillary lymph node dissection, and postoperative radiation. Discussion. Secondary tumors developing in epidermal nevus are rare. To the best of our knowledge, only in two cases including the present case, SCC developed in a solitary epidermal nevus. There is no established clinical guideline for prophylactic removal of epidermal nevus. However, a biopsy should be done if a secondary malignancy is suspected in an epidermal nevus.